THE MORPHONEOTECTONIC STRUCTURE OF THE TRANSITIONAL ZONE BETWEEN THE GORTYNIA MT. HORST AND THE PYRGOS-OLYMPIA BASIN (CENTRAL -WESTERN PELOPONNESE, GREECE) - Fountoulis, I.; Mavroulis, S.; Theocharis, D. (Bulletin of the Geological Society of Greece, 2007)
The present paper aims to the understanding of the neotectonic deformation in areas where no post-alpine sediment occurs. The study area is located at the transitional zone between the horst ofGortynia Mt. (Arcadia) and the Pyrgos-Olympia basin in the central-western Péloponnèse and is tectonically and seismically active. The studied neotectonic faults can be distinguished in low to mid angle faults and high angle faults. The majority of them present striation sets with significant horizontal component that causes the change in the direction and plunge of the fold axes of Pindos unit. The younger and with more active characteristics fault zones are the Lefkohori and Ohthia ones